Peculiarities of the clinical picture and diagnosis of dirofilariasis in the maxillofacial area: a series of cases from practice - Buniatian , Kh.A.; Khotimska, Yu.V.; Kovach , I.V.; Yaroslavska , Yu.Yu.; Bondarenko, O.V.; Nazaryan , R.S. (Medicni Perspektivi, 2024)
Dirofilariasis is a helminthiasis that occurs in carnivorous animals (dogs, cats, foxes, wolves, etc.) and less often in humans, although according to some authors it is believed that the number of infected animals approximately corresponds to the number of infected people. Dirofilariasis of the maxillofacial area is not a widespread condition, its cases are described in short series, therefore, the aim of this work is to share our own experience of managing patients with this rare condition.The work presents our own experience in the management of 14 dirofilariasis patients with lesions of the maxillofacial area, of them there are 3 men and 11 women aged 29 to 54. Most patients sought help in the late autumn, winter and spring periods and only 2 people in the summer period. All patients were examined by a dentist, and an ultrasound examination of the area with a formation was performed. According to the clinical manifestations, the disease began acutely in nine patients and had a picture of inflamed atheroma (2 – in the zygomatic area, 1 – in the parotid, 2 – in the infraorbital area, 2 – in the temporal area, and 2 – in the area of the nasal bridge). All patients were operated on and tumor-like formations in dense membranes were removed, inside which one live nematode 11-18 cm long was found. In 3 observations, fragments of dead, partially lysed nematodes were removed from the oral cavity, the capsules of which imitated a migrating granuloma. According to the location – 5 capsules with dirofilaria were located in the subcutaneous fatty tissue, 3 – in the submucosal layer of the gums fused to the periosteum of the upper jaw, 1 – in the submucous layer of the lower jaw, 2 – in the fibers of the temporalis muscle and 1 – in the fibers of the buccal muscle. In each case, the localization of the nematode was close to the places of accumulation of adipose tissue or large blood vessels. In the postoperative period complex therapy was prescribed, including symptomatic anti-inflammatory and desensitizing agents, and consultation with infectionist was recommended. Thus, according to our observations, dirofilariasis most often affects areas of the face in which there are large vessels and accumulation of fatty tissue. In connection with the prevalence of dirofilariosis in humans and the predominant localization of parasitic infection in the face area, dentists, ophthalmologists and otolaryngologists need to be familiar with this pathology and show definite vigilance. Treatment dirofilariosis patients should be carried out comprehensively, together with parasitologists, with surgical excision of the lesion and appropriate drug therapy.